JAVANESE TRADITIONAL ART-DANCE AS THE IMPLEMENTATION OF CHARACTER EDUCATION OF CHILDREN TO SUPPORT CHILD FRIENDLY SCHOOL - Siti Supeni (RESEARCH FAIR UNISRI, 2020)
The purpose of the research is to: ( I) identify character education of children in various Javanese traditional dances, (2) to analyze the needs, output, problems. and learning objectives of child-friendly schools (CFS) in applying character education based on regional dance by interviewing a dancer trainer and a professional dancer who have experiences in creating and practicing the dances, and (3) to identify types of Javanese traditional dance values inside the dances. the types of research is through literary studies, interviews, surveys, observations, and documentation. To analyze the data, the researchers useResearch & Development. The findings show that (1) identification of charactereducation in various Javanese traditional dance, (2) there are the needs, output, problems, and learning objectives of child-friendly schools (CFS) in implementing character education based on regional dance, and (3) types of Javanese traditional dance values from. Keywords: Javanese Traditional Dance, Character Education, Child-Friendly School